Response to "Comment on 'Tunable Design of Structural Colors Produced by Pseudo‐1D Photonic Crystals of Graphene Oxide' and Thin‐Film Interference from Dried Graphene Oxide Film". Issue 15 (April 2017) - Tong, Liping; Qi, Wei; Wang, Mengfan; Huang, Renliang; Su, Rongxin; He, Zhimin
Abstract : The structural colors produced by pseudo‐1D photonic crystals of graphene oxide originate from the regularly layered structure of GO films, which have been previously reported. For the same observation regarding the tunable color reflection obtained from the dried GO films, Hong et al. suggest a different mechanism to the previously published model.